1989
DOI: 10.1080/00288330.1989.9516351
|View full text |Cite
|
Sign up to set email alerts
|

Prey selection byGalaxias vulgarisin the Hawkins River, New Zealand

Abstract: To determine the extent of prey selection by the nocturnally active fish Galaxias vulgaris, samples of fish, drift, and benthos were collected over a 24-h period in summer in a stream draining the foothills of the Southern Alps in New Zealand. Feeding started after sunset, peaked by midnight, and virtually ceased by midday. Both drifting and benthic foods were consumed, and timing of peak feeding was synchronous with the period of greatest abundance of aquatic drift. Larvae of Austrosimulium spp., Deleatidium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
0
23
1
Order By: Relevance
“…Type B, on the other hand, showed no significant differences between day and night. These findings are not consistent with those of Cadwallader (1975b) and Glova & Sagar (1989) who reported that the feeding of G. vulgaris was correlated with peaks in drift of invertebrate prey at dusk and dawn, respectively. Moreover, they indicate that we may be dealing with species other than that previously described as G. vulgaris.…”
Section: Discussioncontrasting
confidence: 57%
“…Type B, on the other hand, showed no significant differences between day and night. These findings are not consistent with those of Cadwallader (1975b) and Glova & Sagar (1989) who reported that the feeding of G. vulgaris was correlated with peaks in drift of invertebrate prey at dusk and dawn, respectively. Moreover, they indicate that we may be dealing with species other than that previously described as G. vulgaris.…”
Section: Discussioncontrasting
confidence: 57%
“…Food supply for drift-feeding fishes is influenced by current velocity (Chapman 1966;Hearn 1987) and many studies have shown that brown trout are aggressive drift-feeders that compete for positions providing the best access to food (Fausch & White 1981;Fausch 1984;Slaney & Northcote 1974). Since G. vulgaris also feeds on drifting invertebrates (Cadwallader 1975a(Cadwallader , 1975b(Cadwallader , 1975cGlova & Sagar 1989), and has considerable diet overlap with brown trout (Cadwallader 1975b;Glova et al 1992), competition for areas of high current velocity could result in a reduction in food supply for galaxias, particularly smaller individuals which are likely to suffer most in competitive interactions with trout.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat: Occupies a wide range of montane to submontane streams, often in open tussock grassland, apparently less often in forested catchments; distribution extends well out onto the Canterbury Plains to low elevations in some catchments; characteristic of small to moderatesized, swiftly-flowing streams, and typically is found within the boulder/gravel substrates, sometimes within marginal cover, and is sometimes seen in the open by day. Emerges regularly from cover to forage in pools and runs at night (Glova & Sagar 1989), where it is a generalised invertebrate predator. Distribution: G. vulgaris is found widely in the northern and eastern South Island; populations are known from upper tributaries of the Motueka River, which drains north, from upper tributaries of the Wairau River which drains north-east, and from all east-flowing rivers to the south of the Wairau River as far as, and including, the Waitaki River, in North Otago.…”
Section: Colourmentioning
confidence: 99%